Inosine Pranobex Significantly Decreased the Case-Fatality Rate among PCR Positive Elderly with SARS-CoV-2 at Three Nursing Homes in the Czech Republic - Beran, Jiří; Špajdel, Marian; Katzerová, Věra; Holoušová, Alena; Malyš, Jan; Finger Rousková, Jana; Slíva, Jiří (Pathogens (Basel, Switzerland), 2020)
During the COVID-19 pandemic, the elderly population has been disproportionately affected, especially those in nursing homes (NH). Inosine pranobex (IP) has been previously demonstrated to be effective in treating acute viral respiratory infections. In three NH experiencing the SARS-CoV-2 virus epidemic, we started treatment with IP as soon as clients tested PCR+. In Litovel, CZ, the difference in case-fatality rate (CFR) for the PCR+ group using vs. not using IP was statistically significant, and the odds ratio (OR) was 7.2. When comparing all those taking IP in the three NH vs. the non-drug PCR+ group in Litovel, the odds ratio was lower for all three NH, but still significant at 2.9. The CFR in all three tested NHs, age range 75-84, compared to the CFR in all NHs in the Czech Republic, was significantly reduced (7.5% vs. 18%) (OR: 2.8); there was also a significant difference across all age groups (OR: 1.7). In our study with 301 residents, the CFR was significantly reduced (OR: 2.8) to 11.9% (17/142) in comparison to a study in Ireland with 27.6% (211/764). We think the effect of IP was significant in this reduction; nevertheless, these are preliminary results that need larger-scale trials on COVID-19 patients.
Keywords: case-fatality rate; inosine pranobex; COVID-19; acute respiratory viral infection; treatment; nursing homes; natural killer cells